Les dimensions systémiques de la crise des abus dans l'Église catholique et la réforme de l'ecclésiologie courante - Legrand, Hervé (Revue des sciences philosophiques et théologiques, 2020)
The Systemic Dimensions of the Crisis of Abuse in the Catholic Church and the Reform of Current Ecclesiology: In the scarcely evangelical management of sexual offenses committed by clerics, current Catholic ecclesiology has shown systemic weaknesses, which are particularly illustrated by the dichotomy of the " priesthood and laity" in the form favored by Tridentinism. In this framework ordination was understood less as access to the pastorship of a church than as a personal endowment of sacramental powers, lacking any necessary connection to a local church. This model now meets its end in the West, in spite of its recent exaltation, associated with that of the new religious movements. Such a renewal would involve the conferral of greater responsibility upon dioceses and their bishops, and would go hand in hand with an effective synodality, a renewed status of renewal of the clergy, and of a theology of vocation to the ordained ministries, in the sense called for by Saint Pius X.